Swept-source OCT in patients with multiple evanescent white dot syndrome - Felipe Pereira; Luiz H. Lima; Alexandre Gomes B. de Azevedo; Claudio Zett; Michel E. Farah; Rubens Belfort (Journal of Ophthalmic Inflammation and Infection, 2018)
Abstract Background Swept-source optical coherence tomography (SS-OCT) has a higher scanning rate and longer wavelength in comparison with spectral-domain OCT (SD-OCT), allowing an improved imaging of retinal vascular plexuses and choriocapillaris. The present two patients diagnosed with multiple evanescent white dot syndrome (MEWDS) underwent fundus autofluorescence (FAF), en-face SS-OCT, and SS-OCT angiography (OCTA) imaging, and its features were described and correlated. Results The clinical and imaging findings of both cases were consistent with the diagnosis of MEWDS. Color fundus photograph revealed subtle deep retinal white spots in the posterior pole and around the optic disk. FAF showed several hyperautofluorescent lesions corresponding topographically to the subtle deep retinal white lesions observed on color fundus photographs. Cross-sectional SS-OCT showed disruption of the ellipsoid zone (EZ) within the macular area in all study patients. En-face SS-OCT at the level of the outer retina showed lower reflectivity correspondent to the diffuse attenuation due to the EZ disruption on cross-sectional OCT. SS-OCTA demonstrated flow preservation within the retinal vasculature and choriocapillaris. Conclusions SS-OCT imaging allows a better visualization of the choriocapillaris, and its normal appearance in MEWDS may suggest that the outer retina and photoreceptors represent the primary site of inflammation.